Understanding negative self-evaluations in borderline personality disorder: a review of self-related cognitions, emotions, and motives - Winter, Dorina; Bohus, Martin; Lis, Stefanie (Current psychiatry reports, 2017)
Self-conscious emotions, such as guilt, shame, or self-disgust, as well as self-related motives, such as self-enhancement or self-verification, influence how people perceive, evaluate, memorize, and respond to self-related information. They not only influence peoples’ concepts of themselves but may also affect their behavior in social environments. In the current review, we describe alterations of self-related processing in borderline personality disorder (BPD). We chose BPD as an example of a mental disorder of which impairments in self-functioning and identity constitute a major feature. Since terminology used in clinical research on self-referential processing is diverse and often confusing, we start with reviewing some of the main concepts in this area of research using a conceptual framework provided from social psychology. Most studies on self-referential processing in BPD focused on descriptions of self-esteem and revealed a negative self-concept, particularly expressed by explicitly reported low self-esteem. Moreover, self-esteem is unstable in BPD and likely reactive to self-relevant cues. BPD patients are prone to negative emotions with respect to themselves, such as self-disgust and shame. First data point to altered self-related motives, too. In conclusion, although explicit self-esteem is widely studied as a global and trait-like feature of BPD, there is a strong lack of studies that take the complexity of the construct self-esteem into account. Further studies on alterations in self-related processes are required to deepen our understanding of impairments of the self-concept in BPD and enable the improvement of psychosocial therapeutic approaches.
Gesehen am 16.04.2018